Spontaneous tumour lysis syndrome as a rare presentation of thymoma with peripheral blood lymphocytosis - Larry Ellee Nyanti; Sing, Andy Ong Tang; Adam Malik Ismail; Lee, Ping Chew; Tze, Shin Leong (SAGE Publications, 2022)
Tumour lysis syndrome is common in haematological malignancies but is rarely reported in solid tumours. Peripheral blood lymphocytosis is an autoimmune feature of thymomas. We report a 63-year-old female who presented with a mediastinal mass, spontaneous tumour lysis syndrome and a leukoerythroblastic picture on peripheral blood film. Bone marrow aspiration and trephine biopsy ruled out haematological malignancy. Subsequent biopsy of the mediastinal mass confirmed thymoma. This is the first reported case of thymoma with peripheral blood lymphocytosis presenting with spontaneous tumour lysis syndrome. Clinicians are reminded that solid tumours may masquerade as haematological malignancies in the presence of peripheral blood lymphocytosis, hence careful clinical evaluation is needed to differentiate between the two diagnoses.